Paving the Way for Interreligious Dialogue, Tolerance, and Harmony: Following Mukti Aliâs Path - Ismail, Faisal (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2012)
A known Indonesian Muslim scholar Mukti Ali (1923-2004) was very much concerned with dialogue, tolerance, and harmony among the people of different traditions, cultures, and religions. In his many academic works, he stressesed the importance of promoting, strengthening, and maintaining intercultural and interreligious dialogue, tolerance, and harmony. Not only did he produce various academic works, but also made efforts in putting his intercultural and interreligious ideas into practice. Both as a scholar and expert in the comparative study of religions and as Minister of Religious Affairs of the Republic of Indonesia (1971-1978), Mukti Ali endlessly promoted intercultural and interreligiuos diologue, tolerance, and harmony. Realizing that Indonesia is a pluralistic society, Mukti Ali adopted an approach called âagree in disagreementâ in the effort of creating and supporting tolerance, harmony, and security among people of different religious traditions. This paper will highlight the principles and values which Mukti Ali struggled for during his long administrative and academic careers.[Mukti Ali (1923-2004) adalah salah seorang intelektual Muslim ternama di Indonesia. Dia dedikasikan hidupnya untuk menyemai dialog, toleransi dan kehidupan harmonis antar tradisi, budaya dan agama yang beragam. Dalam berbagai karya akademiknya, Mukti Ali selalu menekankan pentingnya kehidupan harmonis dan toleransi antar pemeluk agama dan budaya. Lebih dari itu, dia melampaui hanya sekedar batas pemikiran dengan mengimplementasikan gagasan-gagasannya tersebut. Sebagai seorang ilmuwan dengan keahlian perbandingan agama dan sebagai Menteri Agama RI (1971-1978), Mukti Ali dengan kukuh memperjuangkan dialog, toleransi dan kehidupan harmonis antar agama dan budaya. Mukti Ali sadar, Indonesia adalah negara yang plural, karena itu dia menawarkan pendekatan âagree in disagreementâ untuk menciptakan harmoni dan toleransi tersebut. Tulisan ini mengulas prinsip dan nilai yang diperjuangkan Mukti Ali selama karir akademiknya dan sebagai Menteri Agama.]